The Existence of Nay Subang Larang as a Source of Value Education in Adolescents in Subang District - Fauzan Nugraha, Much Luthfi (International Journal Pedagogy of Social Studies, 2020)
his research is motivated by the number of cases of teenagers from day to day who lose their identity or well behave. This has many reasons for this, one of which is the absence of exemplary figures who provide example in the area where he lives.. This study aims to obtain a descriptive description of the existence of the figure of Nay Subang Larang as a Value Education among Adolescents in Subang Regency, especially in the Village of Nangerang. This research is a qualitative research with a case study approach (case study). Data collection obtained through observation, in-depth interviews and documentation. Participants in this study were 8 teenagers from Nangerang Village who at least had visited the Nay Subang Larang Foundation Site. The results showed that the existence of the figure and the site of Nay Subang Larang itself is quite influential in the behavior of teenagers in the village of Nangerang, although only through stories passed down from generation to generation from their parents. However, this is still considered not optimal for the development of Value Education itself for adolescents in the village of Nangerang due to many things, one of which is the lack of development and expansion of information and communication that is more regulated and documented so that it is more worthy of being used as a means of Value Education especially for adolescents and in general for the wider community.